U–Pb zircon ages for rocks from the Island Lake greenstone belt, Manitoba - Turek, A.; Carson, T. M.; Smith, Patrick E.; Schmus, W. R. Van; Weber, W. (Canadian Journal of Earth Sciences, 1986)
The Archean Hayes River Group of the Island Lake greenstone belt (Superior Province, Sachigo Subprovince) comprises mafic to felsic metavolcanics, subvolcanics, and associated metasedimentary rocks. The Hayes River Group is intruded by granitoid rocks belonging to the early intrusive complex. One such pluton, the Bella Lake tonalite, is intrusive into the metabasalt of the Hayes River Group and has a U–Pb zircon age of 2886 ± 15 Ma. Similar intrusives of this complex, either internal or marginal to the greenstone belt, yield zircon ages of 2801 ± 8 Ma (Pipe Point tonalit) and 2768 ± 22 Ma (Linklater Island prophyry). This suggests that the early intrusive complex was emplaced over an ~ 120 Ma long interval by at least three separate intrusive episodes.Subsequent to the emplacement of the early intrusive complex, the isoclinally folded Hayes River Group and the early intrusive complex were uplifted, eroded, and followed by the unconformable deposition of the Island Lake Group, comprising fluvial to marine metasedimentary rocks. The stratigraphically lower part of the Island Lake Group is bracketed by the 2768 ± 22 Ma age of the Linklater Island porphyry and the 2729 ± 3 Ma age obtained for the late tectonic suite—the Pipe Point quartz diorite and feldspar porphyry. A feldspar quartz porphyry belonging to the post-tectonic intrusive rocks intrudes higher stratigraphic levels and has been dated at 2699 ± 4 Ma (Horseshoe Island quartz feldspar porphyry).